INFORMAL MANAGEMENT OF SERVICES AND PROVIDING HOUSING AND COMMUNAL SERVICES IN THE REGIONS - Y. Slinaykov (Вестник университета)
The article describes the main approaches to the informal management of services and providing housing and communal services in the regions, the analysis of the current practices of management of informal groups with no legally fixed status and other formally regulated signs, and suggestions to approaches to attracting such groups to the management of residential facilities, the improvement of relations with informal groups, based on the allocation of leader, enjoys the greatest authority and respect members of the group regardless of its official status and official powers.